STATE AND REGIONAL OWNED ENTERPRISES : HEAD TO HEAD FINANCIAL PERFORMANCE COMPARISON AT THE YEARS OF 2017-2021 - Syukron Sazly; Aliffah Kusumaningrum; Hasta Herlan; Indra Prana; Intan Kusuma Dewi; Andri Rizko Yulianto (Universitas Muhammadiyah Tangerang, 2023)
The performance of State-Owned Enterprises (BUMN) and Regional-Owned Enterprises (BUMD) is currently the main hope regarding state revenues and one source of regional income, because BUMN and BUMD are national assets and regional assets which are very important as a source of funds for economic recovery. nationally, especially the Covid-19 pandemic that has just passed. The aim of this research is to determine the performance of BUMN compared to the performance of BUMD. Logically, the very large resources of BUMN compared to BUMD should make BUMN's performance better than BUMD and the results are expected to be very different. The data used is BUMN and BUMD financial performance data for five years, namely the 2017-2021 period. In this research, financial performance assessment uses financial ratio indicators, Current Ratio (CR), Debt To Equity Ratio (DER), Debt To Total Asset Ratio (DTA), Net Profit (NPM), Return On Assets (ROA) and Return On Equity (ROE) Test the hypothesis using the Kolomogorov-Sminov for normality-test and t-sample independent-test. The results of this research show that the financial performance of BUMN determined by the Current Ratio (CR), Debt To Equity Ratio (DER), Debt To Total Asset Ratio (DTA), Return On Assets (ROA) and Return On Equity (ROE) is not significantly different from the financial performance of BUMD for the 2017-2021 period.The performance of State-Owned Enterprises (BUMN) and Regional-Owned Enterprises (BUMD) is currently the main hope regarding state revenues and one source of regional income, because BUMN and BUMD are national assets and regional assets which are very important as a source of funds for economic recovery. nationally, especially the Covid-19 pandemic that has just passed. The aim of this research is to determine the performance of BUMN compared to the performance of BUMD. Logically, the very large resources of BUMN compared to BUMD should make BUMN's performance better than BUMD and the results are expected to be very different. The data used is BUMN and BUMD financial performance data for five years, namely the 2017-2021 period. In this research, financial performance assessment uses financial ratio indicators, Current Ratio (CR), Debt To Equity Ratio (DER), Debt To Total Asset Ratio (DTA), Net Profit (NPM), Return On Assets (ROA) and Return On Equity (ROE) Test the hypothesis using the Kolomogorov-Sminov for normality-test and t-sample independent-test. The results of this research show that the financial performance of BUMN determined by the Current Ratio (CR), Debt To Equity Ratio (DER), Debt To Total Asset Ratio (DTA), Return On Assets (ROA) and Return On Equity (ROE) is not significantly different from the financial performance of BUMD for the 2017-2021 period.